Open Skies over the Middle East - Cristea, Anca; Hillberry, Russell; Mattoo, Aaditya (Wiley, 2015)
The dynamism of air traffic markets in the Middle East obscures the persistence of restrictions on international competition. But how important are such restrictions for passenger traffic? This paper uses detailed data on worldwide passenger aviation to estimate the effect of air transport policy on international air traffic. The policy variable is a quantitative measure of the commitments under international agreements. The paper analyses, for the first time, not only bilateral agreements, but also plurilateral agreements such as the one among Arab states. The analysis finds that more liberal policy is associated with greater passenger traffic between countries. Higher traffic levels appear to be driven by larger numbers of city-pairs being served, as well as by more passengers traveling along given routes. To demonstrate the quantitative implication of the estimates, two liberalization scenarios in the Middle East are evaluated. Deepening the plurilateral agreement among Arab states would lead to a 30 per cent increase in intra-regional passenger traffic. Widening the agreement to include Turkey would generate significantly larger gains because current policy vis-à-vis Turkey is much more restrictive. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions http://olabout.wiley.com/WileyCDA/Section/id-820227.html